1
$\begingroup$

I am trying to figure out the solution to the power series

$$\sum_{k=0}^{\infty} k^n p^k$$

where $n$ is a positive integer and $0 \leq p < 1$.

I am sure the series is convergent. When plugging the first few values of $n$ into Wolfram Alpha it is able to come up with a solution very quickly, which indicates to me that there must be a standard way of solving this, however I have not been able to figure out how to proceed.

The first few solutions for specific $n$ are:

\begin{align} \sum_{k=0}^{\infty} k p^k &= \frac{p}{(p-1)^2} \\ \sum_{k=0}^{\infty} k^2 p^k &= \frac{p^2 + p}{-(p-1)^3} \\ \sum_{k=0}^{\infty} k^3 p^k &= \frac{p^3 + 4p^2 + p}{(p-1)^4} \\ \sum_{k=0}^{\infty} k^4 p^k &= \frac{p^4 + 11p^3 + 11p^2 + p}{-(p-1)^5} \\ \sum_{k=0}^{\infty} k^5 p^k &= \frac{p^5 + 26p^4 + 66p^3 + 26p^2 + p}{(p-1)^6} \end{align}

$\endgroup$
2
$\begingroup$

You may find a recurrence without using heavy machinery (a.k.a. special functions):

First, you write $S_n=\sum_{k=0}^\infty k^n p^k$, then differentiate $S_{n-1}$ w.r.t. $p$, you get:

$$\frac{\partial}{\partial p}S_{n-1}=\sum_{k=0}^\infty k^n p^{k-1}=\frac{1}{p}S_n$$

So $S_n=p\frac{\partial}{\partial p}S_{n-1}$. Furthermore, $S_0=\frac{1}{1-p}$

$\endgroup$
2
$\begingroup$

Let's start with

$$f(x)=\sum_{k=0}^\infty e^{kx}=\frac1{1-e^x}$$

Differentiate this $n$ times w.r.t. $x$, applying Faà di Bruno's formula,

$$f^{(n)}(x)=\sum_{k=0}^\infty k^ne^{kx}=\sum_{k=1}^n\frac{k!}{(1-e^x)^{1+k}}B_{n,k}(e^x,e^x,\dots,e^x)$$

where $B_{n,k}$ is an incomplete Bell polynomial with $n-k+1$ variables. Setting $e^x=p$, we get

$$\sum_{k=0}^\infty k^np^k=\sum_{k=1}^n\frac{k!}{(1-p)^{1+k}}B_{n,k}(p,p,\dots,p)$$

$\endgroup$
  • $\begingroup$ Like it a lot +1 $\endgroup$ – Isham Sep 11 '17 at 0:07
  • 1
    $\begingroup$ You know, I've always wondered if anything more can be said about $B_{n,k}(x,x,\dots,x)$ $\endgroup$ – Simply Beautiful Art Sep 11 '17 at 0:16
0
$\begingroup$

The coefficients are given by Euler's triangle.

https://en.wikipedia.org/wiki/Eulerian_number

That is, $$\sum_{k=0}^\infty k^n p^k = \frac{1}{(1-p)^{n+1}} \sum_{m=1}^n A(n,m-1) p^m$$ where $A(n,m)$ is the Eulerian number.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.